PENGARUH KUALITAS PELAYANAN DAN BRAND IMAGE TERHADAP VOLUME PENJUALAN VIVO PADA J-BROSS COMPUTER DAN SMARTPHONE PADANG - Maria Magdalena; Irwansyah Putra (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2023)
This study has a problem formulation, namely whether tangible affects sales volume on J-Bross Computer and Smartphone Padang, reliability affects sales volume on J-Bross Computer and Smartphone Padang, responsiveness affects sales volume on J-Bross Computer and Smartphone Padang, empathy affect sales volume on J-Bross Computer and Smartphone Padang, assurance affect sales volume on J-Bross Computer and Smartphone Padang and whether brand image affects sales volume on J-Bross Computer and Smartphone Padang. This study aims to determine the effect of tangible, reliability, responsiveness, empathy, assurance and brand image on sales volume at J-Bross Computer and Smartphone Padang. This type of research is quantitative research. The sample consists of 74 customers at J-Bross Computer and Smartphone using accidental sampling. Analysis of the data used is multiple linear regression analysis, classical assumption test, and hypothesis testing. The results showed that the Tangible, Responsiveness, Empathy and Brand Image variables partially had no effect on Sales Volume at J-Bross Computer and Smartphone Padang. While the Reliability and Assurance variables have a positive and significant effect on Sales Volume at J-Bross Computer and Smartphone Padang